New scaffolds for type II JAK2 inhibitors overcome the acquired G993A resistance mutation - Arwood, Matthew L; Liu, Yao; Harkins, Shannon K; Weinstock, David M; Yang, Lei; Stevenson, Kristen E; Plana, Olivia D; Dong, Jingyun; Cirka, Haley; Jones, Kristen L; Virtanen, Anniina T; Gupta, Dikshat G; et al. (Cell chemical biology, 2023)
Recurrent JAK2 alterations are observed in myeloproliferative neoplasms, B-cell acute lymphoblastic leukemia, and other hematologic malignancies. Currently available type I JAK2 inhibitors have limited activity in these diseases. Preclinical data support the improved efficacy of type II JAK2 inhibitors, which lock the kinase in the inactive conformation. By screening small molecule libraries, we identified a lead compound with JAK2 selectivity. We highlight analogs with on-target biochemical and cellular activity and demonstrate in vivo activity using a mouse model of polycythemia vera. We present a co-crystal structure that confirms the type II binding mode of our compounds with the "DFG-out" conformation of the JAK2 activation loop. Finally, we identify a JAK2 G993A mutation that confers resistance to the type II JAK2 inhibitor CHZ868 but not to our analogs. These data provide a template for identifying novel type II kinase inhibitors and inform further development of agents targeting JAK2 that overcome resistance.